Otello Gaggi, de l’Italie au goulag - Giorgio Sacchetti (Cahiers d’histoire., 2023)
Otello Gaggi (1896-1945) was an Italian anarchist, an antifascist political refugee in Russia, who ended his days, after untold suffering, in the Soviet Gulag. His adventurous life story, examined through network analysis, in the very different contexts with which he was confronted (from the country of departure to the host country, from his family of origin to the new one that is being formed, from fellow refugees to the different political communities with which he is in contact), gives us an interesting insight into the mechanisms of engagement and disengagement that run through his human life. The article is also based on letters and documents from Italian and Soviet archives.Exile, antifascism, URSS, gulag, victims of stalinism, anarchism, Italy